Holographic optical metasurfaces: a review of current progress. (22nd January 2015) - Genevet, Patrice; Capasso, Federico
Abstract: In this article, we review recent developments in the field of surface electromagnetic wave holography. The holography principle is used as a tool to solve an inverse engineering problem consisting of designing novel plasmonic interfaces to excite either surface waves or free-space beams with any desirable field distributions. Leveraging on the new nanotechnologies to carve subwavelength features within the large diffracting apertures of conventional holograms, it is now possible to create binary holographic interfaces to shape both amplitude phase and polarization of light. The ability of the new generation of ultrathin and compact holographic optical devices to fully address light properties could find widespread applications in photonics.